2020
DOI: 10.1016/j.heliyon.2020.e05710
|View full text |Cite
|
Sign up to set email alerts
|

Does quality stimulate customer satisfaction where perceived value mediates and the usage of social media moderates?

Abstract: Customer is considered as the king in the world of business. The issue of customer satisfaction in electronics home appliances has received greater attention from academics and practitioners. In other words, customer satisfaction is a vital consideration in marketing. With the development of technology, new and innovative electronic home appliances are available in the market. Customers purchase and use the costly electronic home appliances where the satisfaction issue is an important concern. In Bangladesh, w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
61
0
21

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 75 publications
(88 citation statements)
references
References 194 publications
(287 reference statements)
6
61
0
21
Order By: Relevance
“…Following research by An et al, (2021), useful and complete information can create a memorable experience. Hossain et al, (2020) explained that useful, high-quality information would influence consumer perceptions and create customer satisfaction; which supports the findings of this study. Information quality can contribute to the consumer behavior theory because only a few empirical studies have examined the information quality variables.…”
Section: Resultssupporting
confidence: 88%
“…Following research by An et al, (2021), useful and complete information can create a memorable experience. Hossain et al, (2020) explained that useful, high-quality information would influence consumer perceptions and create customer satisfaction; which supports the findings of this study. Information quality can contribute to the consumer behavior theory because only a few empirical studies have examined the information quality variables.…”
Section: Resultssupporting
confidence: 88%
“…In his research on electronic home appliances in Bangladesh, he found that customer perceived value of electronic appliances signifies household users' satisfaction. Very recently, Uzir et al (2020aUzir et al ( , 2021 had similar findings of perceived value on satisfaction in the home appliances market. In mobile phone users, Fazal and Kanwal (2017) that customer value impacts customer satisfaction.…”
Section: The Direct Effect Of Customer Perceived Value On Customer Satisfactionmentioning
confidence: 63%
“…This study used the quality of service to mean the service that a company provides during the purchasing and installation of a product (electronic items) and after-sale service (delivery service, installation service, and repair service). As electronic items need some assistance to be associated with functioning and maintenance (Bei and Chiao 2006), this study denotes the quality of service as service for functioning and maintaining physical products such as installation, repairing, and after-sale service (Uzir et al 2020a).…”
Section: Quality Of Servicementioning
confidence: 99%
See 2 more Smart Citations